Negative electrode material, preparation method thereof and lithium ion battery

CN114628661BActive Publication Date: 2026-10-27BTR NEW MATERIAL GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011459903.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-11
Publication Date
2026-10-27
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

此方法无法保证反应充分进行,副产物较多,颗粒烧结严重,且制备多孔硅主要是纳米硅颗粒堆积而成,结构稳定较差

Benefits of technology

[0026]本发明实施例提供的负极材料的制备方法,具有简单易行、安全且绿色环保的突出优点,可大规模生产。只需N-M材料在高温下与过渡金属卤化物发生反应后去除N-M材料的金属M成分便可以得到大量的多孔硅,产率高,以过渡金属卤化物的化学式为ABx(x=2或3,A包括Sn、Cu、Fe、Zn、Co及Ni中的至少一种,B包括Cl、F及Br中的至少一种),以硅合金为例,硅合金的化学式为MzSi(Z=1~3,M包括Mg和Al)为例,发生的反应方程式为ABx+MzSi=Si+A+MzBx。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628661B_ABST
    Figure CN114628661B_ABST
Patent Text Reader

Abstract

The application discloses a negative electrode material, a preparation method thereof and a lithium ion battery. The negative electrode material is a primary particle. The primary particle comprises a skeleton. The skeleton comprises a main skeleton located in the interior of the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure. A pore channel is formed in the interior of the primary particle. The pore channel extends to the surface of the primary particle. Compared with a secondary porous structure formed by stacking nanoparticles, the porous negative electrode material has the advantages of more stable structure, lower volume expansion, smaller specific surface area and higher porosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode materials, specifically an anode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Currently, the main anode materials for mature commercial lithium-ion batteries are graphite-based carbon materials. However, the theoretical lithium storage capacity of carbon materials is only 372 mAh / g, which cannot meet the demand for high-energy-density materials. Therefore, it is necessary to develop anode materials with higher capacity. Alloy anode materials such as Si, Ge, Sn, Sb, and B can achieve high energy density due to their high mass capacity and low voltage plateau. However, the alloying process of these anode materials with lithium produces huge volume expansion, leading to pulverization of the anode material, loss of electrical contact, and rapid capacity decay. At the same time, the volume expansion of particles can cause swelling of the electrode film, resulting in battery bulging and posing safety hazards. For example, the capacity of Si anode material after complete lithium-ionization can reach 3580 mAh / g, but its volume expansion exceeds 300%. The high volume change effect leads to poor cycle stability, keeping it some distance from practical application.

[0003] Currently, the main methods for preparing nanomaterials are physical and chemical methods. Physical methods mainly include pulverization, mechanical alloying, and evaporation-condensation; chemical methods mainly include vapor-phase precipitation, magnesothermic reduction, and wet chemical reduction aerosol methods. However, these methods for preparing silicon nanomaterials are not only demanding and costly, with complex steps, but also cause serious pollution, involve many toxic substances, and pose significant health risks.

[0004] One method for preparing a low-expansion-rate porous silicon / graphite composite electrode material involves using acid etching of a silicon alloy to create a porous silicon framework. This method requires a large amount of corrosive acid to remove metal elements from the silicon alloy, exhibits strong selectivity for the silicon alloy, has a long reaction time, and causes significant pollution. The hydrogen gas generated by the reaction between the acid and the metal is extremely dangerous, and the equipment requirements are high, making it difficult to scale up. Furthermore, the pore structure of this porous silicon exhibits poor uniformity and orientation, greatly reducing structural integrity and stability, and hindering cycling. Another method utilizes molten salt-assisted magnesia reduction to prepare porous silicon, such as the magnesia reduction of silicon oxide, where a low-melting-point salt acts as an endothermic agent. This method cannot guarantee complete reaction, produces numerous byproducts, suffers from severe particle sintering, and the resulting porous silicon is mainly composed of nano-silicon particles, resulting in poor structural stability. Summary of the Invention

[0005] Therefore, it is necessary to provide a negative electrode material with low expansion, its preparation method, and a lithium-ion battery.

[0006] A negative electrode material, wherein the negative electrode material is a primary particle, the primary particle includes a framework, the framework including a main framework located inside the primary particle and a plurality of branches extending from the main framework to the surface of the primary particle.

[0007] In one embodiment, the main framework is a three-dimensional mesh structure;

[0008] In one embodiment, each branch is an individual grain with a size of 30 nm to 100 nm;

[0009] In one embodiment, the maximum width of the cross-section of the branch is 20nm to 250nm, and the maximum length of the cross-section of the branch is 100nm to 1500nm.

[0010] In one embodiment, the branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires, and nanotubes.

[0011] A negative electrode material, wherein the negative electrode material is a primary particle, the primary particle has a macroporous structure, and the primary particle has channels formed inside the primary particle, the channels extending to the surface of the primary particle.

[0012] In one embodiment, the diameter of the channel is 10 nm to 150 nm; the depth of the channel is 50 nm to 1500 nm.

[0013] A negative electrode material, wherein the negative electrode material is a primary particle, the primary particle having through pores formed inside, and the porosity of the primary particle is not less than 30%.

[0014] In one embodiment, the primary particles are selected from at least one of Si, Ge, Sn, B, and Sb;

[0015] In one embodiment, the median particle size of the primary particles is 0.2 μm to 15 μm;

[0016] In one embodiment, the specific surface area of ​​the primary particles is 5 m². 2 / g~100m 2 / g;

[0017] In one embodiment, the porosity of the primary particles is 30% to 70%;

[0018] In one embodiment, the tap density of the primary particles is 0.2 g / cm³. 3 ~0.8g / cm 3 ;

[0019] In one embodiment, the compacted density of the primary particles is 1.2 g / cm³. 3 ~1.8g / cm 3 ;

[0020] A method for preparing a negative electrode material, the method comprising the following steps:

[0021] A mixture containing NM material and transition metal halides is subjected to a displacement reaction under a protective atmosphere to obtain reaction products, wherein the reaction products include halides of M and transition metals; and

[0022] The halide and transition metal of M are removed to obtain the negative electrode material;

[0023] Wherein, M in the NM material includes at least one of Mg, Al, Li and Ca;

[0024] The N in the NM material includes at least one of Si, Ge, Sn, B, and Sb.

[0025] This preparation method utilizes the reaction of NM material with transition metal halides at high temperature, followed by removal of the metallic M component from the NM material to obtain a porous N anode material. The metal halides generated in the reaction, for example using silicon-magnesium alloy or silicon-aluminum alloy as raw materials, are magnesium or aluminum halides that are in a molten state at the reaction temperature. These molten halides are continuous and provide a connected liquid template for the formation of interconnected nano-N materials. After removing the metal halides, a porous N anode material is obtained. Structurally, nanounits grow along the connected liquid template to form an interconnected framework structure. Removing the template results in primary particles with a macroporous structure, where channels extend to the surface of the primary particles.

[0026] The method for preparing the negative electrode material provided in this invention has the outstanding advantages of being simple, safe, and environmentally friendly, and can be mass-produced. It only requires reacting NM material with a transition metal halide at high temperature and then removing the metal M component of the NM material to obtain a large amount of porous silicon with high yield. The chemical formula of the transition metal halide is AB. x (x = 2 or 3, A includes at least one of Sn, Cu, Fe, Zn, Co, and Ni, and B includes at least one of Cl, F, and Br). Taking silicon alloys as an example, the chemical formula of silicon alloys is M. z Taking Si (Z = 1 to 3, M includes Mg and Al) as an example, the reaction equation is ABx + MzSi = Si + A + MzBx.

[0027] In one embodiment, the NM material is at least one of intermetallic compounds and alloys; for example, it can be a Si-Mg alloy and / or a Si-Al alloy.

[0028] In one embodiment, the D50 of the NM material is 0.1 μm to 15 μm;

[0029] In one embodiment, the chemical formula of the transition metal halide is ABx, where x = 2 or 3, A includes at least one of Sn, Cu, Fe, Zn, Co, Mn, Cr and Ni, and B includes at least one of Cl, F and Br;

[0030] In one embodiment, the molar ratio of the NM material to the transition metal halide is 1:(0.2-2);

[0031] In one embodiment, the heating rate of the heating reaction is 1°C / min to 20°C / min;

[0032] In one embodiment, the heating reaction is carried out at 200℃ to 950℃ for 2 hours to 18 hours.

[0033] In one embodiment, the gas in the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0034] In one embodiment, the method for removing the halide of M and the transition metal from the reaction product is to treat the reaction product in an acid solution and / or a transition metal halide solution.

[0035] In one embodiment, the acid in the acid solution includes at least one of hydrochloric acid, nitric acid, and sulfuric acid;

[0036] In one embodiment, the concentration of the acid solution is 1 mol / L to 5 mol / L, and the treatment time in the acid solution is 1 h to 10 h;

[0037] In one embodiment, the concentration of the transition metal halide solution is 0.5 mol / L to 5 mol / L, and the treatment time in the transition metal halide solution is 1 h to 12 h.

[0038] In one embodiment, the method for preparing the NM material includes:

[0039] M powder and N powder are mixed and heated under a protective atmosphere to obtain NM alloy or NM intermetallic compound;

[0040] In one embodiment, the nitrogen powder has a solid structure and includes at least one of the following: granular, spherical, flake-like, fibrous, and block-like forms.

[0041] In one embodiment, the D50 of the nitrogen powder is 0.1 μm to 15 μm;

[0042] In one embodiment, the molar ratio of N powder to M powder is 1:(1.5~2.5);

[0043] In one embodiment, the molar ratio of N powder to M powder is 1:(0.5~2.5);

[0044] In one embodiment, the heating reaction in the preparation method of the NM material is carried out at 400℃~900℃ for 2h~8h.

[0045] In one embodiment, the heating rate of the heating reaction in the preparation method of the NM material is 1℃ / min to 10℃ / min;

[0046] In one embodiment, the NM material obtained after the reaction is pulverized to a D50 of 0.1 μm to 15 μm;

[0047] In one embodiment, the equipment used for pulverization includes a planetary ball mill, a sand mill, or an air jet mill.

[0048] In one embodiment, the step of mixing the NM material with the transition metal halide further includes the addition of alkali metal halides and / or alkaline earth metal halides.

[0049] In one embodiment, the chemical formula of the alkali metal halide and alkaline earth metal halide is ZBy, wherein y is 1 or 2, Z includes at least one of Li, Na, K, Mg and Ca, and B includes at least one of Cl, F and Br.

[0050] In one embodiment, the molar ratio of at least one of the alkali metal halide and alkaline earth metal halide to the transition metal halide is (0.2-1.5):1.

[0051] In one embodiment, the method includes the following steps:

[0052] M powder is mixed with N powder with a D50 of 0.1 μm to 15 μm, and placed in a protective atmosphere and heated to 400 °C to 900 °C at a rate of 1 °C / min to 10 °C / min for 2 h to 8 h to obtain NM material;

[0053] The NM material was pulverized to obtain alloy powder with a D50 of 0.2 μm to 15 μm. Then, the mixture of ABx and ZBy was mixed with the NM material powder to obtain a mixture.

[0054] The mixture was heated to 200°C to 950°C at a rate of 1°C / min to 20°C / min under a protective atmosphere for 2 h to 18 h to obtain the reaction product;

[0055] The reaction product is treated in an acid solution of 1 mol / L to 5 mol / L for 1 h to 10 h, or in an ABx solution of 0.5 mol / L to 5 mol / L for 1 h to 12 h to remove metal A. The product is then washed with water and dried to obtain the negative electrode material.

[0056] A lithium-ion battery comprising the aforementioned negative electrode material.

[0057] This lithium-ion battery has the advantages of high capacity, high initial efficiency, long cycle life and low expansion.

[0058] The advantages of the present invention will be set forth in part in the description which follows, and in part will be obvious from the description or may be obtained by means of embodiments of the present invention. Attached Figure Description

[0059] Figure 1 A schematic diagram of the skeleton structure of a negative electrode material according to one embodiment;

[0060] Figure 2 The image shown is an electron microscope image of the silicon anode material in Example 1 of this invention.

[0061] Figure 3 The image shows the XRD pattern of the silicon anode material in Example 1 of this invention.

[0062] Figure 4 The first charge-discharge curve of the silicon anode material in Example 1 of this invention;

[0063] Figure 5 The cycling performance curve of the silicon anode material in Example 1 of this invention is shown.

[0064] Figure 6 Here is a scanning electron microscope image of the silicon anode material in Comparative Example 1 of this invention;

[0065] Figure 7 A flowchart illustrating a method for preparing a silicon anode material according to one embodiment;

[0066] Figure 8 A schematic diagram of a method for preparing a silicon anode material according to one embodiment;

[0067] In the figure, 9-channel, 10-main skeleton, 11-branch, 11W-maximum width of the branch's cross-section, 11L-maximum length of the branch's cross-section. Detailed Implementation

[0068] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0069] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other. Several improvements and modifications can be made without departing from the principles of the embodiments of this invention, and these improvements and modifications are also considered to be within the scope of protection of the embodiments of this invention.

[0070] One embodiment provides a negative electrode material to address the high expansion problem of porous negative electrode materials in the prior art. Another embodiment provides a method for preparing the negative electrode material. Yet another embodiment provides a lithium-ion battery comprising the negative electrode material.

[0071] like Figure 1 As shown, one embodiment of a negative electrode material is provided. The negative electrode material is a primary particle. The primary particle includes a framework, which includes a main framework 10 located inside the primary particle and a plurality of branches 11 extending from the primary framework 10 to the surface of the primary particle.

[0072] Please refer to further information. Figure 1 In this embodiment, the primary particles have a macroporous structure, with channels 9 formed inside the primary particles and extending to the surface of the primary particles. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), pores with a diameter greater than 50 nm are called macropores.

[0073] In this embodiment, the negative electrode material is a primary particle. The main skeleton 10 inside the primary particle and the multiple branches 11 extending to the surface of the primary particle are a whole. The entire skeleton structure enhances the electron transfer and ion diffusion of the material, which can effectively release the stress after lithiation and avoid stress concentration at the grain boundaries, which can lead to material cracking and pulverization.

[0074] The pore structure of this negative electrode material, extending to the surface of the primary particles, has the following advantages: First, it improves lithium storage performance while reducing lithium battery expansion. This not only alleviates volume expansion during lithium intercalation but also provides space for internal expansion during lithiation, allowing the electrode material to expand inwards after lithiation, thus reducing the overall electrode film thickness and significantly improving the safety of lithium-ion batteries. Second, it provides channels for electrolyte flow, facilitating electrolyte contact.

[0075] Compared to secondary porous structures formed by the stacking of nanoparticles, the porous anode material prepared in this embodiment has the advantage of a more stable integrated structure, and can also have a smaller specific surface area and higher porosity. This invention uses primary, complete particles with a connected framework, enhancing electron transport and ion diffusion, effectively releasing post-lithiation stress and preventing stress concentration that leads to material pulverization. In contrast, porous materials assembled from secondary particles suffer from stress concentration during lithiation due to the distinct grain boundaries between particles, leading to particle breakage, structural damage, and ultimately, deterioration of electrochemical performance.

[0076] In some implementations, the main framework is a three-dimensional mesh structure;

[0077] In some embodiments, a single branch is a separate grain; there are no obvious grain boundaries between units, and the surface of the primary particle is dispersed with grains, the size of which is 30nm-100nm. Compared with the structure composed of multiple small grains in the prior art, this structure is a single large grain with few grain boundaries. After lithiation, the stress can be better dispersed, avoiding stress concentration that could lead to material damage. At the same time, the crystal plane curves of a single grain are the same, which is more conducive to reducing the relative volume expansion of the material in a certain direction. In contrast, the structure composed of multiple small grains has a relatively large volume expansion and relatively poor structural stability, resulting in poor cycle stability.

[0078] In some implementations, the maximum cross-sectional width 11W of the branch is 20nm-250nm, and the maximum cross-sectional length 11L of the branch is 100nm-1500nm.

[0079] In some embodiments, the branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires, and nanotubes.

[0080] In some embodiments, the diameter of the pores is measured to be 10 nm-150 nm and the depth of the pores is measured to be 50 nm-1500 nm by mercury porosimetry.

[0081] Another embodiment of the negative electrode material is a primary particle with through-pores formed inside. The porosity of the primary particle is not less than 30%. The primary particles of the present invention have high porosity, which can effectively alleviate the volume expansion of silicon negative electrodes of more than 300%. Combined with the advantages of the large-pore through-pore structure, the pore structure can also be kept intact after lithiation. The existing technology has low porosity and contains a lot of micropores and mesopores, which cannot meet the huge volume expansion of silicon. After lithiation, the pores are filled, and due to electrochemical sintering, the pores are eventually blocked, and the porous structure can no longer be maintained.

[0082] The negative electrode material in the above embodiments can be a silicon negative electrode material, a germanium negative electrode material, a tin negative electrode material, a boron negative electrode material, an antimony negative electrode material, etc.; a typical example is a silicon negative electrode material. It can be understood that the primary particles are selected from at least one of Si, Ge, Sn, B, and Sb; its framework can be a silicon framework, a germanium framework, a tin framework, a boron framework, an antimony framework, etc. If a silicon negative electrode material is selected, the silicon negative electrode material is a primary particle, and the primary particle includes a silicon framework, including a main framework located inside the primary particle and multiple branches of the self-framework extending to the surface of the primary particle. The framework structure of Ge, B, Sn, and Sb is similar to the structure of the silicon negative electrode material described above.

[0083] In some embodiments, the median particle size of the primary particles is 0.2 μm to 15 μm, for example, 0.2 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, or 15 μm. Preferably, it is 0.5 μm to 10 μm, and more preferably, it is 1 μm to 5 μm.

[0084] In some implementations, the specific surface area of ​​the primary particles is 5 m². 2 / g~100m2 / g, for example 5m2 / g, 10m 2 / g、20m 2 / g、30m 2 / g、40m 2 / g, 50m 2 / g、60m 2 / g、80m 2 / g or 100m 2 / g, etc. Preferably 10m 2 / g~50m 2 / g.

[0085] In some embodiments, the porosity of the primary particles is 30% to 70%, such as 30%, 35%, 40%, 50%, 55%, 60%, or 70%, preferably 40% to 60%.

[0086] In some embodiments, the tap density of the primary particles is 0.2 g / cm³. 3 ~0.8g / cm 3 For example, 0.2g / cm 3 0.3g / cm 3 0.5g / cm 3 0.6g / cm 3 0.7g / cm 3 or 0.8g / cm 3 Etc. Preferably 0.4 g / cm³ 3 ~0.7g / cm 3 .

[0087] In some embodiments, the compacted density of the primary particles is 1.2 g / cm³. 3 ~1.8g / cm 3 For example, 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 Or 1.8g / cm 3 The preferred value is 1.4 g / cm³. 3 ~1.7g / cm 3 ;

[0088] One embodiment provides a method for preparing a negative electrode material, the method comprising steps S100-S400.

[0089] S100, preparation of NM materials.

[0090] In some embodiments, the NM material is at least one of NM alloy and NM intermetallic compound; wherein, N in the NM material includes at least one of Si, Ge, Sn, B, and Sb; and M in the NM material includes at least one of Mg, Al, Li, and Ca. In specific examples, the NM material can be a Si-Mg alloy, a Si-Al alloy, a Ge-Mg alloy, a Ge-Al alloy, etc.

[0091] In some embodiments, nitrogen powder and magnesium powder are mixed and heated under an inert gas atmosphere to obtain an NM material. In a specific example, silicon powder and magnesium powder are mixed and heated under an inert gas atmosphere to obtain a Si-Mg alloy.

[0092] In some embodiments, the D50 of the N powder is 0.2μm to 15μm, for example, 0.2μm, 0.5μm, 1μm, 3μm, 5μm, 6μm, 8μm, 10μm, 12μm, 13μm or 15μm.

[0093] In some embodiments, the molar ratio of N powder to M powder is 1:(1.5 to 2.5), such as 1:1.5, 1:1.8, 1:2.0, 1:2.1, 1:2.3 or 1:2.5, etc.

[0094] Furthermore, the nitrogen powder has a solid structure and includes at least one of the following: granular, spherical, flake-like, fibrous, and cubic shapes.

[0095] In some embodiments, the heating rate of the heating reaction in the preparation method of the NM material is 1℃ / min to 10℃ / min, for example, 1℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 8℃ / min or 10℃ / min.

[0096] In some embodiments, the heating reaction in the preparation method of the NM material is to keep it at 400℃ to 900℃ for 2h to 8h, with temperatures such as 400℃, 500℃, 600℃, 700℃, 800℃ or 850℃, and times such as 2h, 4h, 5h, 6h, 7h or 8h.

[0097] In some embodiments, the resulting NM material is pulverized after the reaction to a D50 of 0.2 μm to 15 μm, for example, 0.2 μm, 1 μm, 2 μm, 3.5 μm, 5 μm, 7 μm, 10 μm, 12 μm or 15 μm.

[0098] In some embodiments, the equipment used for pulverization includes any one of a planetary ball mill, a sand mill, or an air jet mill.

[0099] Of course, NM materials can also be prepared by other methods, such as high-energy ball milling, vacuum smelting, and hot pressing sintering.

[0100] It is understandable that NM materials can be obtained commercially, so step S100 can be omitted.

[0101] S200. Mix NM material with transition metal halide to obtain a mixture.

[0102] In some embodiments, the NM material may be a Si-Mg alloy (silicon-magnesium alloy) and / or a Si-Al alloy (silicon-aluminum alloy).

[0103] In some embodiments, the D50 of the NM material is 0.1 μm to 15 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm or 15 μm.

[0104] Different types of NM materials can yield framework units of different shapes, including at least one of rod-shaped nanoparticles, nanosheets, nanowires, and nanotubes. For example, different types of silicon alloys can yield framework units of different shapes, including at least one of rod-shaped silicon nanoparticles, silicon nanosheets, silicon nanowires, and silicon nanotubes.

[0105] In some embodiments, the chemical formula of the transition metal halide is ABx, where x = 2 or 3, A includes at least one of Sn, Cu, Fe, Zn, Co and Ni, and B includes at least one of Cl, F and Br.

[0106] In some embodiments, the molar ratio of the NM material to the transition metal halide is 1:(0.2-2), such as 1:0.2, 1:0.5, 1:1, 1:1.2, 1:1.5 or 1:2.

[0107] In some embodiments, the step of mixing the NM material with the transition metal halide further includes at least one of an alkali metal halide and an alkaline earth metal halide.

[0108] In some embodiments, the chemical formula of the alkali metal halide and / or alkaline earth metal halide is ZBy, where y = 1 or 2, Z includes at least one of Li, Na, K, Mg and Ca, and B includes at least one of Cl, F and Br.

[0109] In some embodiments, the molar ratio of at least one of the alkali metal halide and alkaline earth metal halide to the transition metal halide is 1:(0.2-1.5).

[0110] Alkali metal halides and / or alkaline earth metal halides act as molten salt media at high temperatures. On the one hand, they can absorb the heat released during the reaction and maintain the stability of the structure. On the other hand, they can increase the solubility of transition metal halides in them, promote the full reaction, and improve the yield and purity.

[0111] The reasons for the formation of the negative electrode material structure in the embodiments of the present invention are explained as follows: First, if a high-melting-point transition metal chloride (melting point greater than the melting point of the reaction product MzBx) is selected to participate in the dealloying process, the reactant MzBx (e.g., MgCl2, MgF2, or MgBr2) is in a molten state, providing a connected liquid template for the formation of the connected nanoframework, thus ensuring the continuity of the pores in the porous negative electrode material; if an alkali metal halide (ABx) or an alkaline earth metal halide (ZBy) is added, the reaction temperature can be further reduced, so that the melting point of the mixture of MzBx and ABx is lower than the melting point of MzBx itself, achieving the purpose that MzBx can also serve as a liquid template at temperatures below its melting point. 2. When a transition metal chloride with a melting point lower than that of the reaction product MzBx is selected as a reactant, in order to prevent the volatilization of such transition metal chlorides (e.g., ZnCl2 or SnCl2) at high temperatures, we choose to add alkali metal halides (ABx) or alkaline earth metal halides (ZBy) to prevent these transition metal chlorides from volatilizing and to promote the reaction to proceed fully; at the same time, it can lower the melting point of the reaction product MzBx, lower the reaction temperature, and ensure that MzBx is in a molten state, providing a continuous liquid template.

[0112] It is understood that the mixture can be obtained commercially, in which case step S200 can be omitted.

[0113] S300. The mixture is placed in a protective atmosphere to carry out a displacement reaction to obtain a reaction product, the reaction product including a halide of M and a transition metal.

[0114] In some embodiments, the heating rate of the heating reaction is 1°C / min to 20°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, 16°C / min, 18°C / min or 20°C / min.

[0115] In some embodiments, the heating reaction is carried out at 200°C to 950°C for 2 to 18 hours, with temperatures such as 200°C, 235°C, 260°C, 300°C, 400°C, 450°C, 500°C, 600°C, 700°C, 800°C, or 900°C.

[0116] In some embodiments, the gas in the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton, and xenon.

[0117] S400, removing the halides and transition metals of M, yields the negative electrode material.

[0118] In some embodiments, the method for removing the halide of M and the transition metal from the reaction product is to treat the reaction product in an acid solution and / or a transition metal halide solution. The treated product can still be recycled.

[0119] In some embodiments, the acid in the acid solution includes at least one of hydrochloric acid, nitric acid, and sulfuric acid.

[0120] In some embodiments, the concentration of the acid solution is 1 mol / L to 5 mol / L, and the treatment time in the acid solution is 1 h to 10 h. Examples of acid solution concentrations include 1 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 4 mol / L, or 5 mol / L; and treatment times include 1 h, 3 h, 5 h, 6 h, 8 h, 9 h, or 10 h.

[0121] In some embodiments, the concentration of the transition metal halide solution is 0.5 mol / L to 5 mol / L, and the treatment time in the transition metal halide solution is 1 h to 12 h. The concentration of the metal halide solution is, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3.5 mol / L, 4 mol / L, or 5 mol / L; the treatment time is, for example, 1 h, 3 h, 5 h, 6 h, 8 h, 9 h, 10 h, or 11 h.

[0122] The anode material preparation method provided in this invention utilizes the reaction of NM material with transition metal halides at high temperature, followed by removal of M from the NM material to obtain a porous N anode material. Since the metal halides generated in the reaction, taking silicon-magnesium alloy or silicon-aluminum alloy as examples, are magnesium or aluminum halides that are in a molten state at the reaction temperature. The molten halides are continuous and provide a connected liquid template for the formation of interconnected nano-silicon. After removing the metal halides, porous silicon is obtained. Structurally, silicon nanounits grow along the connected liquid template to form an interconnected silicon framework. Removing the template results in a silicon framework with a continuous, interconnected pore structure in three dimensions. This invention relates to a single, complete particle with an interconnected framework, enhancing electron transport and ion diffusion in the material. This effectively releases stress after lithiation, preventing stress concentration that could lead to material pulverization. Existing technologies generally use secondary particles, where primary nanoparticles are assembled or stacked into a large secondary porous silicon particle, such as garnet-shaped, raspberry-shaped, or watermelon-shaped silicon anodes. Because these primary particles have distinct grain boundaries, stress concentration occurs after lithiation, leading to structural instability and ultimately deterioration of electrochemical performance.

[0123] The method for preparing the negative electrode material provided in this invention has the outstanding advantages of being simple, safe, and environmentally friendly, and can be mass-produced. A large amount of porous silicon can be obtained simply by reacting NM material (such as silicon alloy) with a transition metal halide at high temperature and then removing the metal components from the silicon alloy. The yield is high. Taking the chemical formula of the transition metal halide as ABx (x = 2 or 3, where A includes at least one of Sn, Cu, Fe, Zn, Co, and Ni, and B includes at least one of Cl, F, and Br), and the chemical formula of the silicon alloy as MzSi (Z = 1 to 3, where M includes Mg and Al) as an example, the reaction equation is ABx + MzSi = Si + A + MzBx.

[0124] Furthermore, this method utilizes readily available and low-cost raw materials, and the byproducts can be recycled and reused. Inexpensive commercial silicon can be used as a raw material to prepare porous silicon anode materials, resulting in N-type anode materials (Ge, B, Sn, and Sb) with porous structures whose morphology and pore structure are easily controlled. Because the reaction occurs in a liquid environment, it ensures complete reaction, significantly improving yield and product purity.

[0125] By improving the overall process flow and the parameters of each reaction step (such as the type and ratio of reactants, reaction temperature and time), the morphology of the product can be controlled, thereby achieving performance regulation. For example, the alloy composition can be controlled to change the pore size and porosity (generally, the higher the silicon content in a silicon alloy, the smaller the pore size); the reaction time and reaction temperature can be controlled to change the pore depth (generally, the longer the reaction time and the higher the reaction temperature, the deeper the pores; however, the reaction temperature should not exceed 950℃, as excessively high reaction temperatures may cause the generated silicon to react with transition metals to form silicides, such as copper silicide or nickel silicide, degrading the product performance).

[0126] In specific examples, such as Figure 8 As shown, taking silicon anode material as an example, the preparation method of silicon anode material includes the following steps: 1) preparing Si-M alloy; 2) mixing Si-M alloy with transition metal halide to obtain a mixture, wherein M in the Si-M alloy includes at least one of Mg, Al, Li and Ca; 3) placing the mixture in a protective atmosphere to carry out a displacement reaction to obtain a reaction product, wherein the reaction product includes a halide of M, silicon and a transition metal; 4) removing the halide of M and the transition metal to obtain silicon anode material.

[0127] The preparation methods for Ge, B, Sn, and Sb anode materials are similar to those for the porous silicon anode materials.

[0128] In another embodiment, a lithium-ion battery comprises a silicon anode material as described in the first aspect.

[0129] This lithium-ion battery has the advantages of high capacity, long cycle life and low expansion.

[0130] Example 1

[0131] Silicon powder (1 μm) and magnesium powder (1:2 molar ratio) were mixed uniformly and placed in an atmosphere furnace. The mixture was heated to 600 °C at a heating rate of 3 °C / min under argon inert gas protection and held for 6 h to allow for complete reaction, yielding a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain 1 μm silicon-magnesium alloy powder. Then, 1 mol of the silicon-magnesium alloy powder was mixed uniformly with 1 mol of stannous chloride (SnCl2) and 1 mol of sodium chloride (NaCl). The resulting mixture was placed in an argon atmosphere and heated to 750 °C at a heating rate of 3 °C / min, held for 8 h to allow for complete reaction, yielding the reaction product. The reaction product was mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 h, then filtered, washed, and dried to obtain a porous silicon anode material with a median particle size of 1 μm.

[0132] Figure 2 This is an electron microscope image of the porous silicon anode material in this embodiment; Figure 3 This is the XRD pattern of the porous silicon anode material in this embodiment;

[0133] from Figure 2 As can be seen, the prepared silicon anode material is a primary particle. The primary particle includes a silicon framework, comprising a main framework located inside the primary particle and multiple branches extending from the main framework to the surface of the primary particle. The primary particle has a macroporous structure, with channels formed inside the primary particle extending to its surface. Figure 3 The XRD diffraction pattern of the sample after acid washing shows that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there are basically no impurity phases.

[0134] Example 2

[0135] Silicon powder (1 μm) and magnesium powder (1:2 molar ratio) were mixed evenly and placed in an atmosphere furnace. The mixture was heated to 650°C at a heating rate of 5°C / min under argon inert gas protection and held for 3 hours to allow for complete reaction, yielding a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder. 1 mol of the alloy powder was then mixed evenly with 1 mol of copper chloride (CuCl2). The resulting mixture was placed in an argon atmosphere and heated to 800°C at a heating rate of 3°C / min, held for 6 hours to allow for complete reaction, yielding a reaction product. The reaction product was then placed in 1 L of a 2 mol / L ferric chloride solution and mechanically stirred for 3 hours. After filtration, washing, and drying, a porous silicon anode material with a median particle size of 0.5 μm was obtained.

[0136] Example 3

[0137] Silicon powder (1.5 μm) and magnesium powder (1:2 molar ratio) were mixed evenly and placed in an atmosphere furnace. The mixture was heated to 600 °C at a heating rate of 5 °C / min under argon inert gas protection and held for 6 hours to allow for complete reaction, yielding a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain 1 μm silicon-magnesium alloy powder. Then, 1 mol of the alloy powder was mixed evenly with 1 mol of stannous chloride (SnCl2) and 1 mol of lithium chloride (LiCl). The resulting mixture was placed in an argon atmosphere and heated to 400 °C at a heating rate of 3 °C / min, held for 8 hours to allow for complete reaction, yielding the reaction product. The reaction product was then mechanically stirred in 2 L of 1 mol / L hydrochloric acid solution for 3 hours, filtered, washed, and dried to obtain a porous silicon anode material with a median particle size of 1.2 μm.

[0138] Example 4

[0139] Silicon powder (1.5 μm) and aluminum powder (1:1.5 molar ratio) were mixed evenly and placed in an atmosphere furnace. The mixture was heated to 650 °C at a heating rate of 10 °C / min under argon inert gas protection and held for 6 hours to allow for complete reaction, yielding a silicon-aluminum alloy. The silicon-aluminum alloy was ball-milled to obtain 2 μm silicon-aluminum alloy powder. 1 mol of the alloy powder was then mixed evenly with 0.8 mol of stannous chloride (SnCl2). The resulting mixture was placed in an argon atmosphere and heated to 600 °C at a heating rate of 5 °C / min, held for 6 hours to allow for complete reaction, yielding a reaction product. The reaction product was then mechanically stirred in 1 L of 1 mol / L hydrochloric acid solution for 2 hours, filtered, washed, and dried to obtain a porous silicon anode material with a median particle size of 2 μm.

[0140] Example 5

[0141] Silicon powder (1.5 μm) and aluminum powder (1:2 molar ratio) were mixed evenly and placed in an atmosphere furnace. The mixture was heated to 650 °C at a heating rate of 10 °C / min under argon inert gas protection and held for 6 hours to allow for complete reaction, yielding a silicon-aluminum alloy. The silicon-aluminum alloy was ball-milled to obtain 1 μm silicon-aluminum alloy powder. Then, 1 mol of the alloy powder was mixed evenly with 1 mol of stannous bromide (SnBr2). The resulting mixture was placed in an argon atmosphere and heated to 650 °C at a heating rate of 5 °C / min, held for 6 hours to allow for complete reaction, yielding the reaction product. The reaction product was then mechanically stirred in 1 L of 1 mol / L hydrochloric acid solution for 5 hours, followed by filtration, washing, and drying to obtain a porous silicon anode material.

[0142] Example 6

[0143] 2.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2 and placed in an atmosphere furnace. Under the protection of argon inert gas, the mixture was heated to 650 °C at a heating rate of 10 °C / min and held for 6 h to allow for complete reaction and obtain a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain 1 μm silicon-magnesium alloy powder. Then, 1 mol of the alloy powder was mixed evenly with 1 mol of stannous bromide (SnBr2) and 1 mol of potassium bromide (KBr). The resulting mixture was placed in an argon atmosphere and heated to 450 °C at a heating rate of 5 °C / min and held for 6 h to allow for complete reaction and obtain the reaction product. The reaction product was placed in 1 L of 1 mol / L hydrochloric acid solution and mechanically stirred for 4 h. After filtration, washing, and drying, a porous silicon anode material was obtained.

[0144] Example 7

[0145] Except for adjusting the molar ratio of silicon powder to magnesium powder to 1:5, the other methods and conditions are the same as in Example 1.

[0146] Example 8

[0147] Except for adjusting the temperature of the reaction between the silicon-magnesium alloy and stannous chloride to 300°C, the other methods and conditions are the same as in Example 1.

[0148] Example 9

[0149] Except for adjusting the temperature of the reaction between the silicon-magnesium alloy and stannous chloride to 850°C, the other methods and conditions are the same as in Example 1.

[0150] Example 10

[0151] Silicon powder (1.5 μm) and aluminum powder (1:1.5 molar ratio) were mixed evenly and placed in an atmosphere furnace. The mixture was heated to 650 °C at a heating rate of 10 °C / min under argon inert gas protection and held for 6 hours to allow for complete reaction, yielding a silicon-aluminum alloy. The silicon-aluminum alloy was ball-milled to obtain 2 μm silicon-aluminum alloy powder. 1 mol of the alloy powder was then mixed evenly with 0.8 mol of zinc chloride (ZnCl2). The resulting mixture was placed in an argon atmosphere and heated to 600 °C at a heating rate of 5 °C / min, held for 6 hours to allow for complete reaction, yielding a reaction product. The reaction product was then mechanically stirred in 1 L of 1 mol / L hydrochloric acid solution for 2 hours, filtered, washed, and dried to obtain a silicon anode material with a median particle size of 2 μm.

[0152] Example 11

[0153] 1 μm germanium (Ge) powder and magnesium powder were mixed evenly at a molar ratio of 1:2 and placed in an atmosphere furnace. Under the protection of argon inert gas, the mixture was heated to 650 °C at a heating rate of 3 °C / min and held for 6 h to allow for complete reaction and obtain a germanium-magnesium alloy. The germanium-magnesium alloy was ball-milled to obtain 1 μm germanium-magnesium alloy powder. Then, 1 mol of germanium-magnesium alloy powder was mixed evenly with 1 mol of stannous chloride (SnCl2) and 1 mol of sodium chloride (NaCl). The resulting mixture was placed in an argon atmosphere and heated to 750 °C at a heating rate of 3 °C / min and held for 8 h to allow for complete reaction and obtain the reaction product. The reaction product was mechanically stirred in 1 mol / L hydrochloric acid solution for 2 h, then filtered, washed, and dried to obtain a porous germanium anode material with a median particle size of 1 μm.

[0154] Example 12

[0155] Boron (B) powder (1 μm) and magnesium powder were mixed uniformly at a molar ratio of 2:1 and placed in an atmosphere furnace. The mixture was heated to 600℃ at a heating rate of 3℃ / min under argon inert gas protection and held for 6 hours to allow for complete reaction, yielding a boron-magnesium alloy. The boron-magnesium alloy was ball-milled to obtain 1 μm boron-magnesium alloy powder. Then, 1 mol of the boron-magnesium alloy powder was mixed uniformly with 1 mol of zinc chloride (ZnCl2) and 1 mol of potassium chloride (KCl). The resulting mixture was placed in an argon atmosphere and heated to 750℃ at a heating rate of 3℃ / min, held for 8 hours to allow for complete reaction, yielding the reaction product. The reaction product was mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 hours, then filtered, washed, and dried to obtain a porous boron anode material with a median particle size of 1 μm.

[0156] Example 13

[0157] Tin (Sn) powder (1 μm) and magnesium powder were mixed evenly at a molar ratio of 1:2 and placed in an atmosphere furnace. The mixture was heated to 650 °C at a heating rate of 3 °C / min under argon inert gas protection and held for 6 h to allow for complete reaction, yielding a tin-magnesium alloy. The tin-magnesium alloy was ball-milled to obtain 1 μm tin-magnesium alloy powder. Then, 1 mol of the tin-magnesium alloy powder was mixed evenly with 1 mol of zinc chloride (ZnCl2) and 1 mol of potassium chloride (KCl). The resulting mixture was placed in an argon atmosphere and heated to 750 °C at a heating rate of 3 °C / min, held for 8 h to allow for complete reaction, yielding the reaction product. The reaction product was mechanically stirred in a 1 mol / L hydrochloric acid solution for 2 h, then filtered, washed, and dried to obtain a porous tin anode material with a median particle size of 1 μm.

[0158] Example 14

[0159] 1 μm tellurium (Sb) powder and magnesium powder were mixed uniformly at a molar ratio of 1:1 and placed in an atmosphere furnace. Under the protection of argon inert gas, the mixture was heated to 600 °C at a heating rate of 3 °C / min and held for 6 h to allow for complete reaction and obtain a tellurium-magnesium alloy. The tellurium-magnesium alloy was ball-milled to obtain 1 μm tellurium-magnesium alloy powder. Then, 1 mol of tellurium-magnesium alloy powder was mixed uniformly with 1 mol of copper chloride (CuCl2) and 1 mol of sodium chloride (NaCl). The resulting mixture was placed in an argon atmosphere and heated to 750 °C at a heating rate of 3 °C / min and held for 8 h to allow for complete reaction and obtain the reaction product. The reaction product was mechanically stirred in 1 mol / L hydrochloric acid solution for 2 h, then filtered, washed, and dried to obtain a porous tellurium anode material with a median particle size of 1 μm.

[0160] Comparative Example 1

[0161] This comparative example is Example 1 of patent CN 105399100 A. The scanning electron microscope image of the prepared nanoporous silicon is shown below. Figure 6 Porous silicon structures cannot be obtained.

[0162] Comparative Example 2

[0163] Except for the absence of stannous chloride, the methods and conditions are the same as in Example 1.

[0164] Performance testing:

[0165] The negative electrode materials of Examples 1-14 and Comparative Examples 1-2 were tested using the following methods:

[0166] The tap density was tested using a Canta AutoTap tap density meter.

[0167] The specific surface area of ​​the material was tested using the Tristar3000 fully automated specific surface area and porosity analyzer from Micron Instruments, Inc.

[0168] Porosity: The porosity was tested using an AutoPore Ⅳ9510 fully automatic mercury porosimeter from the American company, Micron Instruments. Powder compaction density: The compaction density was tested using a domestic powder compaction density tester, FT-100F, in accordance with the standard GBT24533-2009.

[0169] First-week performance test of coin cell battery: The first-week test of coin cell battery was conducted on the Blue Electric CT2001A battery testing system, with a charge and discharge current of 0.05C.

[0170] Cyclic test: Cyclic test was performed on the coin cell using the Blue Electric CT2001A battery testing system with a current of 0.2C for 150 cycles.

[0171] The test results are shown in Tables 1 and 2:

[0172] Table 1

[0173]

[0174] Table 2

[0175]

[0176]

[0177] In the table, "-" indicates none.

[0178] Figure 4 This is the first charge-discharge curve of the porous silicon anode material in this embodiment. The charge-discharge current is 0.05C, and a half-cell test is used. Figure 5 The circuit performance curve of the porous silicon anode material in this embodiment is shown, with a charge / discharge current of 0.2C. Figure 4 and Figure 5 As can be seen, the material has high initial charge-discharge efficiency and excellent cycle performance. Examples 7-9, by adjusting the reactant molar ratio, reaction temperature, and time, still yielded porous silicon, but the performance was somewhat lower than that of Example 1.

[0179] By comparing Example 7 with Example 1, the molar ratio of silicon powder to magnesium powder increased, the porosity increased, the tap density decreased, the first efficiency decreased, and the energy density decreased.

[0180] Compared with Example 1, Example 8 showed that the temperature was too low, the reaction was insufficient, the structure was not uniform, the internal and external pore structures were inconsistent, the structure was unstable, and the cycle performance was reduced.

[0181] Compared with Example 1, Example 9 shows that excessively high temperature leads to larger grain size, coarser silicon skeleton, easier pulverization, reduced first-time efficiency, and reduced cycle performance.

[0182] Comparing Example 1 and Comparative Example 1, the porous silicon obtained in Example 1 has a smaller specific surface area than that in Comparative Example 1. In Comparative Example 1, zinc chloride was used and the reaction temperature was 300°C. The magnesium chloride produced at this temperature was in solid particulate form, which served as a solid template. As a result, the final porous silicon was formed by the accumulation of nano-silicon particles, leading to a larger specific surface area and a reduced first-efficiency. In contrast, the reaction temperature in Example 1 was 750°C, and the magnesium chloride produced was in a continuous liquid state, which served as a connected liquid template. This resulted in a skeletal structure for the porous silicon, which greatly reduced the specific surface area of ​​the material and improved the first-efficiency.

[0183] By comparing Example 1 and Comparative Example 2, it was found that porous silicon could not be prepared without the addition of stannous chloride.

[0184] Examples 11-14 prepared porous germanium, porous boron, porous tin, and porous tellurium with framework structures by changing the raw materials using a method similar to that in Example 1.

[0185] The applicant declares that the detailed method of the present invention is illustrated by the above embodiments, but the present invention is not limited to the above detailed method, that is, it does not mean that the present invention must rely on the above detailed method to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A negative electrode material, characterized in that, The negative electrode material is a primary particle, and the primary particle includes a framework, which includes a main framework located inside the primary particle and multiple branches extending from the main framework to the surface of the primary particle. Each branch is an individual grain; the main framework is a three-dimensional network structure. The branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires and nanotubes; The primary particle has channels formed inside it, and the channels extend to the surface of the primary particle.

2. The negative electrode material according to claim 1, characterized in that, The size of the grains is 30nm~100nm.

3. The negative electrode material according to claim 1, characterized in that, The maximum width of the cross-section of the branch is 20nm~250nm, and the maximum length of the cross-section of the branch is 100nm~1500nm.

4. The negative electrode material according to claim 1, characterized in that, The primary particles are selected from at least one of Si, Ge, Sn, B, and Sb.

5. The negative electrode material according to claim 1, characterized in that, The median particle size of the primary particles is 0.2µm to 15µm.

6. The negative electrode material according to claim 1, characterized in that, The specific surface area of ​​the primary particles is 5m². 2 / g ~100m 2 / g.

7. The negative electrode material according to claim 1, characterized in that, The porosity of the primary particles is 30% to 70%.

8. The negative electrode material according to claim 1, characterized in that, The tap density of the primary particles is 0.2 g / cm³. 3 ~ 0.8g / cm 3 .

9. The negative electrode material according to claim 1, characterized in that, The compacted density of the primary particles is 1.2 g / cm³. 3 ~ 1.8g / cm 3 .

10. A method for preparing a negative electrode material as described in any one of claims 1-9, characterized in that, The method includes the following steps: A mixture containing NM material and transition metal halides is subjected to a displacement reaction under a protective atmosphere to obtain reaction products, wherein the reaction products include halides of M and transition metals; and The halide and transition metal of M in the reaction product are removed to obtain the negative electrode material; Wherein, M in the NM material includes at least one of Mg, Al, Li and Ca; The N in the NM material includes at least one of Si, Ge, Sn, B, and Sb.

11. The method according to claim 10, characterized in that, The NM material is at least one of intermetallic compounds and alloys.

12. The method according to claim 10, characterized in that, The D50 of the NM material is 0.1 μm ~ 15 μm.

13. The method according to claim 10, characterized in that, The chemical formula of the transition metal halide is AB. x Where x = 2 or 3, A includes at least one of Sn, Cu, Fe, Zn, Co, Mn, Cr and Ni, and B includes at least one of Cl, F and Br.

14. The method according to claim 10, characterized in that, The molar ratio of the NM material to the transition metal halide is 1:(0.2~2).

15. The method according to claim 10, characterized in that, The heating rate of the displacement reaction is 1℃ / min ~ 20℃ / min.

16. The method according to claim 10, characterized in that, The displacement reaction is carried out at 200℃ ~ 950℃ for 2h ~ 18h.

17. The method according to claim 10, characterized in that, The protective atmosphere contains at least one of nitrogen, helium, neon, argon, krypton, and xenon.

18. The method according to claim 10, characterized in that, The method for removing the halide of M and the transition metal from the reaction product is to treat the reaction product in an acid solution and / or a transition metal halide solution.

19. The method according to claim 18, characterized in that, The acid in the acid solution includes at least one of hydrochloric acid, nitric acid, and sulfuric acid.

20. The method according to claim 18, characterized in that, The concentration of the acid solution is 1 mol / L to 5 mol / L, and the treatment time in the acid solution is 1 h to 10 h.

21. The method according to claim 18, characterized in that, The concentration of the transition metal halide solution is 0.5 mol / L to 5 mol / L, and the treatment time in the transition metal halide solution is 1 h to 12 h.

22. The method according to claim 10, characterized in that, The preparation method of the NM material includes: M powder and N powder are mixed and heated under a protective atmosphere to obtain NM alloy or NM intermetallic compound; The nitrogen powder has a solid structure and includes at least one of the following: granules, spheres, flakes, fibers, and cubes.

23. The method according to claim 22, characterized in that, The D50 of the nitrogen powder is 0.1 μm ~ 15 μm.

24. The method according to claim 22, characterized in that, The molar ratio of N powder to M powder is 1:(1.5~2.5).

25. The method according to claim 22, characterized in that, The heating reaction in the preparation method of the NM material is carried out at 400℃ ~ 900℃ for 2h ~ 8h.

26. The method according to claim 22, characterized in that, The heating rate of the heating reaction in the preparation method of the NM material is 1℃ / min ~ 10℃ / min.

27. The method according to claim 22, characterized in that, The resulting NM material is then pulverized to a D50 of 0.1µm to 15µm after the reaction.

28. The method according to claim 27, characterized in that, The equipment used for pulverization includes planetary ball mills, sand mills, or air jet mills.

29. The method according to claim 10, characterized in that, The mixture also contains alkali metal halides and / or alkaline earth metal halides.

30. The method according to claim 29, characterized in that, The chemical formulas of the alkali metal halides and alkaline earth metal halides are ZB. y , where y is 1 or 2, Z includes at least one of Li, Na, K, Mg and Ca, and B includes at least one of Cl, F and Br.

31. The method according to claim 29, characterized in that, The molar ratio of at least one of the alkali metal halide and alkaline earth metal halide to the transition metal halide is (0.2~1.5):

1.

32. A lithium-ion battery, characterized in that, The lithium-ion battery comprises the negative electrode material as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Porous silicon negative material of lithium ion battery and preparation method and application of material

    CN103165874A

  • Preparation method for nanoporous silicon

    CN105399100A